Increasing the production of Lab Lab, the ideal food for successful culture of the milkfish, Chanos chanos (Forsskal - Bensam, P (Indian Journal of Fisheries, 2011)
The favourite food item of the milkfish in the South-East Asian countries, where it has been cultured, is the benthic complex of periphyton called Lab Lab (Pillai 1962, Bardach et al. 1972). This is composed of microscopic organisms, dominated chiefly by blue-green algae like Phormidium and Oscillatoria, diatoms like Navicuta and Pleurosigma, amphipods, nematodes, et